Penyesuaian Anggaran Belanja Organisasi Perangkat Daerah di Masa Pandemi Covid-19 - Safitri, Felila; Suparno, Suparno (Manajemen Inovasi Bisnis dan Strategi, 2024)
This study aims to examine the budget adjustments made by the District Work Unit (SKPK) in Nagan Raya during the COVID-19 pandemic by taking a case study of the Nagan Raya Regency Social Service in 2020. This study uses primary and secondary data. Primary data sources were obtained from documentation and interviews, and secondary data consisted of direct and indirect expenditure data, as well as budget realization reports. The results of the study show that the Social Service has adjusted its budget due to the COVID-19 pandemic. Furthermore, in the implementation of the budget after the adjustment process, it was found that about 25 percent of the budget was not realized due to the limited time available for the Social Service to execute the budget, which significantly impacted the Social Service's ability to achieve its vision and mission and to provide maximum service to the community.